2004
DOI: 10.1089/hum.2004.15.921
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Skin Equivalents for Gene Therapy of Recessive Dystrophic Epidermolysis Bullosa

Abstract: We have shown that retroviral vectors efficiently transfer the 9-kb collagen type VII cDNA into keratinocytes of dogs with recessive dystrophic epidermolysis bullosa (RDEB) and achieve correction of the RDEB phenotype in vitro. As a next step toward gene therapy applications, we have assessed the suitability of retroviral vectors to transduce human collagen type VII cDNA into primary human RDEB keratinocytes and generate transplantable autologous skin equivalents. The transduced RDEB keratinocytes permanently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 47 publications
2
72
2
3
Order By: Relevance
“…Recently, our labs have addressed the correction of RDEB in a clinically relevant manner. 13 In our setting, correction was achieved by using a conventional retroviral vector and a cultured skin equivalent to accomplish permanent epidermal regeneration in patients. 4 Our results evidenced that the size of the retroviral genome does not hamper its efficient packaging into the viral capsid and generation of infectious viral particles.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 99%
“…Recently, our labs have addressed the correction of RDEB in a clinically relevant manner. 13 In our setting, correction was achieved by using a conventional retroviral vector and a cultured skin equivalent to accomplish permanent epidermal regeneration in patients. 4 Our results evidenced that the size of the retroviral genome does not hamper its efficient packaging into the viral capsid and generation of infectious viral particles.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 99%
“…Subjects with RDEB develop painful blisters and wounds on the skin and mucous membranes, leading to a shortened life expectancy due to infection, organ failure, or squamous cell carcinoma (SCC). Preclinical RDEB studies have suggested various treatment strategies for the disease, such as direct virus-based (Woodley et al, 2004b), protein-based (Woodley et al, 2004a;Remington et al, 2009), and cell-based therapies including bone marrowderived cells (Tolar et al, 2009) and genetically modified keratinocytes (Chen et al, 2002;Ortiz-Urda et al, 2002;Gache et al, 2004) or fibroblasts (Ortiz-Urda et al, 2003;Woodley et al, 2003;Kern et al, 2009). The promise suggested by this body of preclinical research points to the emergence of new treatments for RDEB beyond currently available palliative wound care.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, estos modelos ofrecen la posibilidad de utilizar queratinocitos y/o fibroblastos humanos a los que previamente se les ha introducido una modificación genética. Esta estrategia ha permitido validar a nivel preclínico abordajes de terapia génica ex vivo 44,45,47 o conseguir la regeneración de la epidermis a partir de una única célula madre epidérmica 51 . El programa SkinModel-CM contempla, también, desarrollar estrategias de sobre-expresión y silenciamiento de los genes que codifican endoglina y podoplanina, para analizar sus efectos en la regeneración y arquitectura de la piel, así como en procesos neoplásicos y de cicatrización de heridas.…”
Section: Sistemas Quiméricos De Ratones Inmunodeficientes Con Piel Huunclassified